'Unbearable suffering': a qualitative study on the perspectives of patients who request assistance in dying. Issue 12 (24th September 2011) - Dees, Marianne K; Vernooij-Dassen, Myrra J; Dekkers, Wim J; Vissers, Kris C; van Weel, Chris
Abstract : Background: One of the objectives of medicine is to relieve patients' suffering. As a consequence, it is important to understand patients' perspectives of suffering and their ability to cope. However, there is poor insight into what determines their suffering and their ability to bear it. Purpose: To explore the constituent elements of suffering of patients who explicitly request euthanasia or physician-assisted suicide (EAS) and to better understand unbearable suffering from the patients' perspective. Patients and methods: A qualitative study using in-depth face-to-face interviews was conducted with 31 patients who had requested EAS. The grounded theory approach was used to analyse the data. Results: Medical, psycho-emotional, socio-environmental and existential themes contributed to suffering. Especially fatigue, pain, decline, negative feelings, loss of self, fear of future suffering, dependency, loss of autonomy, being worn out, being a burden, loneliness, loss of all that makes life worth living, hopelessness, pointlessness and being tired of living were constituent elements of unbearable suffering. Only patients with a psychiatric (co)diagnosis suffered unbearably all the time. Conclusions: Unbearable suffering is the outcome of an intensive process that originates in the symptoms of illness and/or ageing. According to patients, hopelessness is an essential element of unbearable suffering. Medical and social elements may cause suffering, but especially when accompanied by psycho-emotional and existential problems suffering will become 'unbearable'. Personality characteristics and biographical aspects greatly influence the burden of suffering. Unbearable suffering can only be understood in the continuum of the patients' perspectives of the past, the present and expectations of the future.